Implikasi Pembatalan Perkawinan Terhadap Status dan Pembagian Harta Bersama Menurut Hukum Perdata Indonesia - Wijaya, Dody; Wahyudi, Wahyudi (Sekolah Tinggi Ilmu Syariah Wal Aqidah Ash-Shofa Manonjaya, 2026)
This study analyzes the implications of marriage annulment on the status and division of joint property under Indonesian civil law. The research focuses on the dichotomy between the legal fiction in Article 28 of the Marriage Law, which states that everything applies